2017
DOI: 10.1038/nature25007
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase III limits longevity downstream of TORC1

Abstract: SummaryThree distinct RNA polymerases (Pols) transcribe different classes of genes in the eukaryotic nucleus1. Pol III is the essential, evolutionarily conserved enzyme that generates short, non-coding RNAs, including transfer RNAs (tRNAs) and 5S ribosomal RNA (rRNA)2. Historical focus on transcription of protein-coding genes has left the roles of Pol III in organismal physiology relatively unexplored. The prominent regulator of Pol III activity, Target of Rapamycin kinase Complex 1 (TORC1), is an important lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
150
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(154 citation statements)
references
References 49 publications
4
150
0
Order By: Relevance
“…Considering that tRNAs and 5S rRNAs account for more than 15% of total RNA (Moir & Willis, ), it is straightforward to suggest that Pol III inhibition saves energy expenditure and cellular resources. Consistent with this notion, limiting Pol III is shown to extend lifespan in budding yeast, worms, and fruit flies (Filer et al, ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Considering that tRNAs and 5S rRNAs account for more than 15% of total RNA (Moir & Willis, ), it is straightforward to suggest that Pol III inhibition saves energy expenditure and cellular resources. Consistent with this notion, limiting Pol III is shown to extend lifespan in budding yeast, worms, and fruit flies (Filer et al, ).…”
Section: Discussionmentioning
confidence: 71%
“…Because calorie or dietary restriction inhibits the TORC1 pathway to extend lifespan (Kaeberlein & Kennedy, ), one can speculate that Maf1‐mediated Pol III inhibition could extend lifespan. Consistent with this, a recent study reported that Pol III inhibition extends lifespan in Saccharomyces cerevisiae , Caenorhabditis elegans , and Drosophila (Filer et al, ). Interestingly, limiting Pol III activity in intestinal cells is sufficient to extend lifespan in nematode worms and fruit flies, and Maf1‐overexpression reduces tRNA transcripts in fruit fly guts, which accompanies extended lifespan.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…mTOR also associates with TFIIIC at Pol III‐transcribed genes to relieve their repression by Maf1 . Interestingly, mTOR itself was also found to be enriched at Pol III genes , a phenomenon recently linked to the processes of aging and longevity . Genome‐wide ChIP‐sequencing experiments performed in our laboratory with primary liver tissue subsequently revealed that mTOR binds to nearly to all Pol III‐dependent genes and, in addition, that the kinase can be detected at the Polr3e promoter, demonstrating the potential for a comprehensive role for mTOR in Pol III‐dependent gene transcription .…”
Section: Mtor Signaling Impacts Gene Expression By All Three Rna Polymentioning
confidence: 72%
“…Indeed, evidence has been accumulating for almost two decades that mTOR and some components of mTORC1 and mTORC2 complexes such as Raptor, Rictor, RHEB, SIN1, and S6K are indeed found in the nucleus , and more recently that nmTOR directly controls gene transcription. The physical presence and/or activity of mTOR in the nucleus has been reported by numerous groups using a wide range of techniques in organisms ranging from yeast to human , including primary tissues such as mouse liver and human tumors of various origins . In particular, the recent genome‐wide localization of nmTOR at specific loci by chromatin immunoprecipitation coupled with deep sequencing (ChIP‐seq) assays , the subcellular localization of mTOR‐tagged enhanced green fluorescent protein (EGFP) using lifetime imaging microscopy , and the dynamic visualization of mTORC1 activity in living cells using a fluorescence resonance energy transfer (FRET)‐based activity biosensor , have provided not only further evidence of mTOR nuclear localization but solidified the notion that nmTOR is an authentic participant of the mTOR signaling pathway.…”
Section: Introductionmentioning
confidence: 99%